2019
DOI: 10.1007/s40121-019-0245-2
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Pertussis, an Under-Recognized Health Burden and Rationale for Maternal Immunization: A Systematic Review of South and South-East Asian Countries

Abstract: Pertussis is an under-recognized cause of neonatal morbidity and mortality. To review information on the epidemiology and disease burden of neonatal pertussis in South and Southeast Asian countries, a systematic literature review of three bibliographic databases was undertaken. Peer-reviewed original studies on neonatal pertussis epidemiology and burden published since 2000, with a geographical scope limited to South and Southeast Asian countries, were included. Data were systematically extracted based on para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 48 publications
0
9
0
1
Order By: Relevance
“…Within the current epidemiologic context of pertussis, many countries in which the number of cases have increased in mainly newborns and infants not receiving primary doses because of age (Fabricius et al, 2018;Agrawal et al, 2019) have once again begun discussion on neonatal vaccination and its possible implementation (Lumbreras Areta et al, 2019). Neonatal immunization would provide an early protection for newborns and infants, thus narrowing the critical period of vulnerability intrinsic to routine vaccination schedules that start later in life.…”
Section: Discussionmentioning
confidence: 99%
“…Within the current epidemiologic context of pertussis, many countries in which the number of cases have increased in mainly newborns and infants not receiving primary doses because of age (Fabricius et al, 2018;Agrawal et al, 2019) have once again begun discussion on neonatal vaccination and its possible implementation (Lumbreras Areta et al, 2019). Neonatal immunization would provide an early protection for newborns and infants, thus narrowing the critical period of vulnerability intrinsic to routine vaccination schedules that start later in life.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggested that early identification and treatment of B. pertussis could shorten the duration of paroxysmal cough (27,28), and antibiotics against pertussis could limit the severity of disease if started in the catarrhal phase (27,29). In addition, several systematic reviews confirmed the safety and effectiveness of maternal pertussis vaccination during pregnancy (30)(31)(32). Therefore, it is important to early recognize and initiate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The disease is still endemic worldwide and can have severe complications in young infants [36]. Review of epidemiological data on neonatal pertussis published between 2000 and 2018 has shown that the burden of neonatal pertussis and related complications is high in South and Southeast Asia [37]. The number of pertussis cases observed per year has increased in infants younger than three months old.…”
Section: Maternal Tdap Vaccinationmentioning
confidence: 99%
“…The number of pertussis cases observed per year has increased in infants younger than three months old. Indeed, infant mortality rates due to pertussis ranges between 5.6% and 14.7% in the region [37]. In India, review of 36 pertussis cases admitted to the pediatric intensive care unit showed that 27.7% of those infected were infants below six weeks of age, the youngest age to receive the first dose of the tetanus-diphtheria-pertussis vaccine [36,38].…”
Section: Maternal Tdap Vaccinationmentioning
confidence: 99%